Trans-Equatorial Migration Routes, Staging Sites and Wintering Areas of a High-Arctic Avian Predator: The Long-tailed Skua (Stercorarius longicaudus) - Gilg, Olivier; Moe, Børge; Hanssen, Sveinn Are; Schmidt, Niels Martin; Sittler, Benoît; Hansen, Jannik; Reneerkens, Jeroen; Sabard, Brigitte; Chastel, Olivier; Moreau, Jérôme; Phillips, Richard A.; Oudman, Thomas; et al. (PLOS ONE, 2013)
The Long-tailed Skua, a small (<300 g) Arctic-breeding predator and seabird, is a functionally very important component of the Arctic vertebrate communities in summer, but little is known about its migration and winter distribution. We used light-level geolocators to track the annual movements of eight adult birds breeding in north-east Greenland (n = 3) and Svalbard (n = 5). All birds wintered in the Southern Hemisphere (mean arrival-departure dates on wintering grounds: 24 October-21 March): five along the south-west coast of Africa (0–40°S, 0–15°E), in the productive Benguela upwelling, and three further south (30–40°S, 0–50°E), in an area extending into the south-west Indian Ocean. Different migratory routes and rates of travel were documented during post-breeding (345 km d−1 in late August-early September) and spring migrations (235 km d−1 in late April) when most birds used a more westerly flyway. Among the different staging areas, a large region off the Grand Banks of Newfoundland appears to be the most important. It was used in autumn by all but one of the tracked birds (from a few days to three weeks) and in spring by five out of eight birds (from one to more than six weeks). Two other staging sites, off the Iberian coast and near the Azores, were used by two birds in spring for five to six weeks. Over one year, individuals travelled between 43,900 and 54,200 km (36,600–45,700 when excluding staging periods) and went as far as 10,500–13,700 km (mean 12,800 km) from their breeding sites. This study has revealed important marine areas in both the south and north Atlantic Ocean. Sustainable management of these ocean basins will benefit Long-tailed Skuas as well as other trans-equatorial migrants from the Arctic.